PENGEMBANGAN INSTRUMEN PENILAIAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI ZAT ADITIF DAN ADIKTIF - Siska Baharizki; Wahyu Budi Sabtiawan; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study was typed of research and development (R&D) which aims to provide valid and reliable instruments for assessing critical thinking skills in additive and addictive matter. The data collection technique used critical thinking skill test method in form of 12 items essay questions and quisionare method in form of validation and analysis sheets aimed at expert lectures and science teacher. The test instrument that has been developed was tested to obtain empirical validation on 26 students of SMP Negeri 1 Gresik who were randomly selected. The obtained data were further analyzed descriptively using qualitative and quantitative analysis techniques. The data analysis results which have been carried out, shows that the developed test instrument is eligible for measuring students critical thinking skill. This is evidenced from the results of the theoretical validation by experts over the developed instrument had a very good categorized mode by 5. In addition, the developed instrument has a valid criteria (rcount > rtable) and highly categorized Cronbach Alpha reliability level by 0,889. Thus, it is expected that the next investigator could explore the research and development stage until the end, namely expanding the distribution with large-scale research subjects. Moreover, it is expected that from this study results might be used as a reference to the science teachers to measure the students critical thinking skills.